SYEKH SITI JENAR, MANUNGGALING KAWULA GUSTI DAN KONTEKS KEKINIAN KITA - Abdul Muaz (Jurnal An-Nufus, 2021)
This article discusses the teachings of Sheikh Siti Jenar from the perspective of the Wujudiyyah doctrine in the literature of Sufism. In the Indonesian Sufism-Philosophy discourse, Sheikh Siti Jenar is one of the controversial sufis, both from her origins, teachings, to her death. For this reason, we try not to mention in detail the pros and cons that adorn him; rather it focuses on his teachings and sayings in a Sufistic context and their relevance to today's life. This paper uses the method of analyzing the literature of Syekh Siti Jenar's thoughts descriptively. Some points that can be summarized from this research are: Sheikh Siti Jenar's teachings are identical to the conception of embodiment al-Hallaj, the principle of Manunggaling Kawula Gusti taught by Sheikh Siti Jenar trying to correct the meaning of our monotheism values ??which are too shallow esoteric, and above all that his teachings are still relevant if we want to delve deeper into our modern life today..